Pemanfaatan Media Sosial Sebagai Alat Pemasaran dalam Meningkatkan Kinerja Usaha Kerajinan Perhiasan Desa Celuk- Sukawati, Kabupaten Gianyar -Bali - Nilna Muna (Journal on Education, 2023)
The use of social media as a marketing tool to encourage the business performance of micro, small, and medium enterprises in jewelry crafts. This research is social media as a marketing tool for micro, small and medium enterprises (MSMEs) in the jewelry handicraft industry. The discussion was "To what extent can the use of social media to maximize MSME marketing increase selling power so that it can improve the performance of jewelry crafts in Gianyar Regency?" This research was conducted using descriptive qualitative methods to answer research questions. In-depth interviews with informants related to research questions that resulted in the conclusion that first, social media has not been able to directly improve the business performance of jewelry craft MSMEs in Celuk Village, Sukawati District, Gianyar Regency. Second, the use of social media in improving performance must be supported by innovation and adaptation to better information technology. Third, MSME players in the jewelry handicraft industry have made it easier for consumers, especially in Bali Province, to shop and choose jewelry handicraft products online without having to leave home. This study aims to examine the potential of jewelry craft MSME business actors in Gianyar Regency to boost their output through social media marketing.